2020
DOI: 10.9734/ijpr/2020/v5i330137
|View full text |Cite
|
Sign up to set email alerts
|

Malarial Related Myopathies: A Rhabdomyolysis Story

Abstract: Malaria is amongst the most prevalent and epidemiologically relevant global parasitic protozoan infections. It is infecting millions of people annually, especially in south east Asia and sub Saharan Africa. Its morbidity and mortality still cannot be controlled entirely and elimination is still far away. Children and pregnant women are among the most vulnerable group in the population. Its pathobiology have related to cause direct or indirect deleterious effect on the patient’s skeletal muscle, named rhabdomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Fluid resuscitation has been widely used to treat rhabdomyolysis, and it was also the most commonly used method in our study. Although fluid therapy is emphasized by consensus [5,37,38], other treatment methods are still controversial. Dawley [37] reported that management consists of rapidly aggressive intravenous resuscitation to maintain urine output and limited use of bicarbonate for acidosis and mannitol for oliguria, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid resuscitation has been widely used to treat rhabdomyolysis, and it was also the most commonly used method in our study. Although fluid therapy is emphasized by consensus [5,37,38], other treatment methods are still controversial. Dawley [37] reported that management consists of rapidly aggressive intravenous resuscitation to maintain urine output and limited use of bicarbonate for acidosis and mannitol for oliguria, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although fluid therapy is emphasized by consensus [5,37,38], other treatment methods are still controversial. Dawley [37] reported that management consists of rapidly aggressive intravenous resuscitation to maintain urine output and limited use of bicarbonate for acidosis and mannitol for oliguria, respectively. Michelsen et al [38] reported guidelines that recommend early fluid resuscitation using crystalloids but not the routine use of diuretics, mannitol, alkalization, or RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike approaches to more common parasitic agents, e.g., malaria with no matter how obscure the clinical manifestations, cases of FLA are often missed because they are rarely recognized. [21] FLA is also not part of normal flora or common human microbiome, so their existence in the human body, especially in deep organ is often hidden and hard to detect [22]. A fast and efficient diagnosis is mandatory, however it depends on two variables: (1) the familiarity of practitioner with the symptomatology and treatment of FLA infections, and also (2) the sufficiency and appropriate clinical material (qualitatively and quantitatively) in order to be processed for making a fast and definitive diagnosis [23].…”
Section: Fig 6 Complete Life Cycle Of Balamuthia Mandrillaris [12]mentioning
confidence: 99%